Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Pendidikan, Pemuda Dan Olahraga (Disdikpora) Kabupaten Karawang - Dede Yulia; Anggi Pasca Arnu (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to determine the partial and simultaneous influence between organizational culture, employee work environment on the performance of the employees of the Department of Education, Youth and Sports (DISDIKPORA), Karawang Regency. The method used in this research is descriptive and verification methods. The population in this study were 267 employees of the Office of Education, Youth and Sports (DISDIKPORA) Karawang Regency. The sample used in this study amounted to 157 employees. The sampling technique used in this study is a simple random sampling technique. The results showed that there was a partial influence of 28.2% between Organizational Culture on employee performance and there was a partial influence between the work environment and employee performance by 19.3%. Meanwhile, the simultaneous influence between organizational culture and work environment on employee performance is 47.5% and the influence of other variables outside the model is 52.5%. 47.5%. Keywords: Organizational Culture, Work Environment, Employee Performance.